2016
DOI: 10.1097/cej.0000000000000172
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline prevents nonalcoholic steatohepatitis-related liver pre-neoplasms by inhibiting hepatic inflammation and lipogenesis

Abstract: Nonalcoholic steatohepatitis (NASH) has gained attention as a hepatic manifestation associated with metabolic syndrome and one of the causes for chronic liver damage leading to hepatocellular carcinoma. Although no standard medicinal treatment for NASH has been established, pentoxifylline (PTX), a medicine used to improve circulation, has recently been reported to ameliorate the histopathological appearance of NASH. In the present study, we investigated the effects of PTX on the development of NASH and diethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…This result is consistent with previous studies, which have demonstrated that the reduction in TNF-α following treatment with chemopreventive agents led to the suppression of obesity-related colorectal tumorigenesis [13,34]. Recent studies have also reported that PTX inhibited obesity-related steatohepatitis and the subsequent liver tumorigenesis by the suppression of pro-inflammatory cytokines such as TNF-α [19,35]. These data, together with the results of the present study, strongly suggest that attenuation of chronic inflammation using PTX might be a promising method for the prevention of obesity- and inflammation-related carcinogenesis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is consistent with previous studies, which have demonstrated that the reduction in TNF-α following treatment with chemopreventive agents led to the suppression of obesity-related colorectal tumorigenesis [13,34]. Recent studies have also reported that PTX inhibited obesity-related steatohepatitis and the subsequent liver tumorigenesis by the suppression of pro-inflammatory cytokines such as TNF-α [19,35]. These data, together with the results of the present study, strongly suggest that attenuation of chronic inflammation using PTX might be a promising method for the prevention of obesity- and inflammation-related carcinogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…A recent paper reported that PTX ameliorated the histopathological appearance of non-alcoholic steatohepatitis (NASH), which is closely associated with obesity and metabolic syndromes, in a randomized placebo-controlled trial [18]. In a mouse model, PTX also prevented NASH-related liver tumorigenesis through the attenuation of chronic hepatic inflammation [19]. In addition, PTX has been reported to suppress tumor necrosis factor (TNF)-α synthesis and oxidative stress and improve the pathophysiological conditions of chronic inflammatory diseases [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other PDE inhibitor‐treated groups, pentoxifylline and cilostazol showed a significant decrease in lipid profile compared with the sildenafil group. The prominent effect of pentoxifylline and cilostazol on lipid profiles may be due to their ability to inhibit lipogenesis . However, the antihypercholesterolemic effect of sildenafil is conducted via increasing the transfer of blood cholesterol to be used in bile synthesis .…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, pentoxifylline showed relative more suppressive effects on the inflammatory biomarkers compared with cilostazol treatment. To be explained, studies of Shirakamia et al, showed that pentoxifylline has additive directly inhibited TNF‐α expression in the livers of rats with NASH fed a HFD . Oxidative stress and inflammation are also instigators of insulin resistance involved in NAFLD pathogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…Complementary DNA (cDNA) was amplified from 1.5 µg of total RNA from each sample using High-Capacity cDNA Reverse Transcription Kit (Applied Biosystems, Foster City, CA, USA). The primers used for amplifying Cox-2, Ccl-2, Tnf-a, F4/80, catalase, Gpx-4, Sod-1, Sod-2, Igf-1, Igf-2, Igfbp-3, and 18S-specific genes were previously reported [50,51] or as follows: Igf-1, forward 5 -TCG GCC TCA TAG TAC CCA CT-3 , reverse 5 -ACG ACA TGA TGT GTA TCT TTA TTG C-3 ; Igf-2, forward 5 -ACC TTC GGC CTT TGT CTG GTA-3 , reverse 5 -CGA AGG CCA AAG AGA TGA GA-3 ; and Igfbp-3 forward 5 -GAC GAC GTA CAT TGC CTC AG-3 , reverse 5 -GTC TTT TGT GCA AAA TAA GGC ATA-3 . Real-time PCR was performed using a Light Cycler (Roche Diagnostics Co., Indianapolis, IN, USA) with FastStart Essential DNA Green Master (Roche Diagnostics Co., Indianapolis, IN, USA).…”
Section: Mrna Extraction and Qrt-pcr Analysismentioning
confidence: 99%